2018
DOI: 10.18632/oncotarget.25328
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of azacitidine is independent of molecular and clinical characteristics - an analysis of 128 patients with myelodysplastic syndromes or acute myeloid leukemia and a review of the literature

Abstract: Azacitidine is the first drug to demonstrate a survival benefit for patients with MDS. However, only half of patients respond and almost all patients eventually relapse. Limited and conflicting data are available on predictive factors influencing response. We analyzed 128 patients from two institutions with MDS or AML treated with azacitidine to identify prognostic indicators. Genetic mutations in ASXL1, RUNX1, DNMT3A, IDH1, IDH2, TET2, TP53, NRAS, KRAS, FLT3, KMT2A-PTD, EZH2, SF3B1, and SRSF2 were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 74 publications
1
42
2
2
Order By: Relevance
“…At present, there is not enough data to support that mutation status can predict response to DNMTIs. While some studies found correlations between TET2 mutations and improved response and DNMT3A mutations and poor response, further studies have not supported these associations (Traina et al , ; Bejar & Steensma, ; Jung et al , ; Kuendgen et al , ) . Somatic mutation status may, however, predict duration of response to therapy.…”
Section: Ngs Results and Treatment Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is not enough data to support that mutation status can predict response to DNMTIs. While some studies found correlations between TET2 mutations and improved response and DNMT3A mutations and poor response, further studies have not supported these associations (Traina et al , ; Bejar & Steensma, ; Jung et al , ; Kuendgen et al , ) . Somatic mutation status may, however, predict duration of response to therapy.…”
Section: Ngs Results and Treatment Implicationsmentioning
confidence: 99%
“…Mutations in SF3B1 are present in approximately 20% of MDS cases. There are well‐established associations between SF3B1 mutations and MDS subtypes: MDS with ring sideroblasts and single or multi‐lineage dysplasia (MDS‐RS‐SLD, MDS‐RS‐MLD, respectively; Malcovati et al , ) and the related MDS/myeloproliferative neoplasm (MPN) overlap disease, MDS/MPN with ring sideroblasts and thrombocytosis (MDS/MPN‐RS‐T)(Savona et al , ; Kuendgen et al , ). SF3B1 mutations are commonly found in the presence of MDS with ring sideroblasts and overlap considerably with del 5q (Papaemmanuil et al , ; Yoshida et al , ; Visconte et al , ; Malcovati et al , ).…”
Section: Commonly Mutated Genes In Mdsmentioning
confidence: 99%
“…101 Furthermore, certain high-risk subgroups may benefit from HMA such as those with TP53 mutations, or complex karyotypes. [102][103][104] A head-to-head comparison between decitabine and "317" as the preferred induction strategy for older patients is currently being tested in the InDACtion trial. 105 The BCL-2 inhibitor venetoclax in combination with HMA 106 or low-dose cytarabine 107 has shown promising results.…”
Section: Non-anthracycline Induction and Treatment Strategiesmentioning
confidence: 99%
“…In this regard, such diseases have emerged in new therapeutic targets. Chemical agents such as 5-azacytidine and 5-aza-2′-deoxycytidine, which inhibit methylation by binding to and inhibiting DNMT enzyme, are now being tested in phase II-III studies [35][36][37][38]. Furthermore, use of oligonucleotides that bind to promoter regions at specific gene level and perform gene inhibition is seen as approaches that may contribute to cancer treatments [39][40][41].…”
Section: Resultsmentioning
confidence: 99%